Herbaceous species mitigate the influence of wetting-drying cycles on the infiltration potential of clayey soil - Gao, Feng; Li, Xindong; Cui, Wenxin; Liu, Qi; Xia, Zhenyao; Kang, Chao (Frontiers in Plant Science, 2026)
IntroductionWetting-drying cycles significantly influence soil hydro-mechanical properties, thereby playing a crucial role in the assessment of geological hazards. However, their effects on the infiltration potential of vegetated clayey soils remain poorly understood.MethodsThis study examined low-plasticity clay in experimental boxes with four treatments (Cynodon dactylon, Lolium perenne, Festuca arundinacea, and an unplanted control), each with three replicates. Following five wetting-drying cycles, desiccation crack patterns, soil aggregation, hydraulic parameters, pore-water distribution, and infiltration characteristics were systematically quantified at each cycle.ResultsGrass species significantly enhanced fine particle aggregation and effectively suppressed desiccation crack formation during the alternate wetting-drying processes. Bare soils exhibited progressive decreases in adsorbed/movable water ratio, saturated moisture content, and residual moisture content with the successive wetting-drying cycles, whereas opposite trends were observed in vegetated soils. After five wetting-drying cycles, the stable infiltration rate of bare soils improved significantly (83.17 ± 5.19%), and that of vegetated soils were lower (7.69%–18.06%). The increased permeability of bare soils is primarily controlled by the variations of movable/adsorbed water ratio and the dimensionless soil-water characteristic curves parameter (α) induced by the wetting-drying cycles, whereas in vegetated soils, this enhancement results from the persistent effects of roots on soil physicochemical properties.DiscussionThe presence of grass species effectively mitigates the influence of wetting-drying cycles on the infiltration potential of clayey soil, this can serve as a reference for ecological measures of engineering slope or soil waste landfill.